Protein-based composite materials. - Kaplan, David, 1953-; Hu, Xiao.; Cebe, Peggy.; Weiss, Anthony S.; Omenetto, Fiorenzo. (Tufts University. Tisch Library., 2016)
Protein-based composite biomaterials have been actively pursued as they can encompass a range of physical properties to accommodate a broader spectrum of functional requirements, such as elasticity to support diverse tissues. By optimizing molecular interfaces between structural proteins, useful composite materials can be fabricated as films, gels, particles, and fibers, as well as for electrical and optical devices. Such systems provide analogies to more traditional synthetic polymers yet with expanded utility due to the material's tunability, mechanical properties, degradability, biocompatibility, and functionalization, such as for drug delivery, biosensors, and tissue regeneration.